A randomized practical behavioural trial of curriculum-based advocacy training for individuals with traumatic brain injury and their families. (6th December 2015) - Brown, Allen W.; Moessner, Anne M.; Bergquist, Thomas F.; Kendall, Kathryn S.; Diehl, Nancy N.; Mandrekar, Jay
Abstract: Primary objective : To test whether a curriculum-based advocacy training programme improves advocacy behaviour when compared to a matched group engaged in self-directed advocacy activities. Research design : Community-based randomized practical behavioural trial. Methods and procedures : Adults with moderate–severe TBI 1 or more years post-injury and their family members were recruited in Minnesota (4 years), Iowa and Wisconsin (each 3 years) and randomized into a curriculum-based or self-directed advocacy training group. Both groups met on the same day, at separate locations in the same city, once per month for 4 consecutive months. Main outcomes and results : Pre–post written and video testimony were rated using the Advocacy Behaviour Rating Scale (ABRS). Mean ABRS scores increased after intervention in both groups (curriculum n  = 129, self-directed n  = 128), but there was no significant difference in this increase between groups. When groups were combined, a significant pre–post improvement in mean ABRS scores was observed. Conclusions : Curriculum-based advocacy training was not superior to a self-directed approach in improving ABRS scores. A significant improvement in expression of an advocacy message was observed when intervention groups were combined. These findings suggest that bringing together like-minded motivated individuals is more important than programme structure or content in changing advocacy behaviour.